2015
DOI: 10.1097/id.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

Early Periimplant Tissue Healing on 1-Piece Implants With a Concave Transmucosal Design

Abstract: Within the limits of the present study, a concave transmucosal design in 1-piece implants was associated with a short vertical value of biological width and promoted a mechanical interlocking of the implant body at the connective tissue and marginal bone levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
(12 reference statements)
1
11
0
Order By: Relevance
“…The concave profile of these abutments is critical during the formation of peri‐implant soft tissues, in fact some clinical investigations have shown that concave or convergent profiles at transmucosal level lead to better esthetic results not only at the level of soft tissues but also at the level of hard tissues . This is clearly explained by some histological studies on an animal model that showed that the transmucosal concavities guide peri‐implant collagen fibers, during their formation, to position themselves within the concavity itself, thus migrating in a coronal sense, contributing not only to have better and healthier peri‐implant tissues, but also to a more stable marginal bone with less initial marginal resorption …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concave profile of these abutments is critical during the formation of peri‐implant soft tissues, in fact some clinical investigations have shown that concave or convergent profiles at transmucosal level lead to better esthetic results not only at the level of soft tissues but also at the level of hard tissues . This is clearly explained by some histological studies on an animal model that showed that the transmucosal concavities guide peri‐implant collagen fibers, during their formation, to position themselves within the concavity itself, thus migrating in a coronal sense, contributing not only to have better and healthier peri‐implant tissues, but also to a more stable marginal bone with less initial marginal resorption …”
Section: Discussionmentioning
confidence: 99%
“…36,37 This is clearly explained by some histological studies on an animal model that showed that the transmucosal concavities guide periimplant collagen fibers, during their formation, to position themselves within the concavity itself, thus migrating in a coronal sense, contributing not only to have better and healthier peri-implant tissues, but also to a more stable marginal bone with less initial marginal resorption. 38,39 The most obvious limitation of this study is the limited follow-up time and the number of patients treated; however, the study is still ongoing and we will report the data with a longer follow-up and more patients in a forthcoming publication. Prospective data obtained from a larger pool of patients and after a longer observation period would allow to increase the significance of the results of this study and to better evaluate their external validity.…”
Section: Procedures Timementioning
confidence: 99%
“…The concave neck provides an increased space for soft tissues maturation and the establishment of a biological width. The incremented contact area provided by the concave design also provides major volume; it has been shown that, besides being shorter, the soft tissue seal around the implant is thicker [ 21 ]. The distance of 1,5 mm between the IAJ and the implant shoulder can be considered as a “safe distance” that prevents potentially harmful periodontal flora, which is known to extend apically from the epithelial junction to a maximum of 1,1 mm [ 22 ], from reaching the first bone to implant contact.…”
Section: Discussionmentioning
confidence: 99%
“…Three histologic studies showed promising results in terms of crestal bone preservation and soft tissues maturation with this concave transmucosal design. Bolle et al, in a histometric study on dogs, found evidence of some bone apposition on the implant shoulder during the healing: the marginal bone was at the level of the implant shoulder after 3 weeks and 0,18 mm above it after 18 weeks [ 21 ]. On the other hand, there have been controversial results about the dimensions of the biological width around this neck configuration: according to Huh and Bolle, this dimension is lower in the vertical plane compared to flared neck designs, while Kim et al found no differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation